A case of diverticulitis in the horizontal part of the duodenum - Ujita, Wataru; Takuma, Kensuke; Namiki, Moeko; Watanabe, Koji; Yamada, Yuto; Hara, Seiichi; Kishimoto, Yui; Ito, Ken; Okano, Naoki; Igarashi, Yoshinori (Nippon Shōkakibyō Gakkai zasshi, 2021)
A 38-year-old woman was referred to our department to investigate epigastric discomfort. Laboratory studies showed increases in the peripheral white blood cell count and the level of C-reactive protein. Abdominal computed tomography depicted inflammation and a mass in the horizontal part of the duodenum. To observe it directly, we performed esophagogastroduodenoscopy (EGD), but it was very difficult to reach the lesion. Therefore, we performed enteroscopy by using SIF-H290S (Olympus Europa SE & Co. KG, Hamburg, Germany), which revealed a diverticulum containing food residue in the horizontal part of the duodenum. Using grasping forceps, we removed the food residue. The patient recovered over the next several days. Endoscopic therapy was thus effective for duodenal diverticulitis caused by food residue, but attention to technique was necessary.